Analysis of The Use And Maintenance of Lifeboats To Support Safety On Board The Mv. Tanto Subur II - Agung Nugroho; Firdaus Sitepu; Damoyanto Purba; Muhammad Dahri (International Journal of Science and Environment (IJSE), 2026)
This study analyzes the use and maintenance of enclosed lifeboats to support safety on board the MV. Tanto Subur II. The background of this study is based on the importance of lifeboat readiness as the main safety tool according to SOLAS and Planned Maintenance System (PMS) provisions, however, problems are still found in the implementation of maintenance in the field. The purpose of this study is to analyze the implementation of enclosed lifeboat maintenance and assess its suitability with the PMS in supporting operational readiness during emergencies. This study uses a descriptive qualitative method. The study population is all crew members involved in the operation and maintenance of lifeboats, with samples consisting of the Chief Officer, Third Officer, Third Engineer, and Electrician through a purposive sampling technique. The research instruments include interview guidelines, observation sheets, and documentation. The data analysis technique uses the Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. The results of the study indicate that although maintenance and procedures have been implemented according to the PMS, obstacles are still found such as gear brake damage, limited equipment, old engine age, and low frequency of lifeboat drills. The conclusion of the study shows that the readiness of enclosed lifeboats is not optimal so that continuous improvement of maintenance, supervision, and training is needed.